Factors Affecting Business Continuity In The Smes Sector - Dela Ayu Kaswadi; Noor Huda; Krisna Puji Rahayu; Intania Sari; Retno Setyowati; Novia Kurniawati; Aris Eddy Sarwono (International Journal of Science, Technology & Management, 2021)
This study aims to analyze the effect of E-Marketing and Financial Inclusion variables on the sustainability of Lurik Weaving SMEs in Klaten Regency, Central Java. The data source of this research uses primary data sources by using questionnaires. Respondents in this study were Lurik weaving SMEs, totaling 57 SMEs. The sampling technique uses a purposive technique with a convenience approach. The results of the analysis show that the use of the E Marketing strategy can improve the level of sustainability of Lurik Weaving SMEs, while the financial inclusion variable does not have a significant impact on the sustainability of SMEs. In addition, this analysis also uses control variables for the age of SME managers and the length of business of SMEs. The results of the analysis show that the length of business for SMEs can have an impact on the sustainability of SMEs.